Assessing the prevalence of self-medication among healthcare workers before and during the 2019 SARS-CoV-2 (COVID-19) pandemic in Kenya - David Onchonga; Joshua Omwoyo; Duke Nyamamba (Elsevier, 2020)
Background: Self-medication plays a key role in public health as it influences both negatively and positively on the health of individuals and the existing healthcare systems. This is especially the case during public health emergencies like the 2019 SARS-CoV-2 disease. Objectives: The study aimed at assessing the prevalence of self-medication before and during the outbreak of COVID-19 pandemic among healthcare workers and its associated factors. Methods: Stratified sampling was used to select 379 study respondents. The authors developed an online questionnaire, pretested and submitted to various online professional groups of different cadres of healthcare workers. Collected data was analysed using descriptive and inferential statistics. The data was presented in tables, graphs, percentages, and cross-tabulation with different variables. Multivariable logistic regression was used to ascertain factors that influence an individual's desire to self-medicate and associations were considered significant at p < 0.05. Results: The overall prevalence of self-medication increased from 36.2% (n = 137) before the pandemic to 60.4% (n = 229) during the pandemic. The respondents' gender, level of education, age, marital status, participation in physical activity, and drug reaction events, were significantly associated with self-medication before and during the outbreak (P < 0.05). Multivariable logistic regression analyses showed that participants engaging in physical activities, working during the day and being healthy were less likely to self-medicate (p < 0.01). Conclusion: Self-medication is an important health issue, especially during the COVID-19 pandemic. Continuous awareness creation and sensitization could help in reducing self-medication practices among healthcare workers.